A LITERATURE REVIEW ON THE IMPACT OF ARTIFICIAL INTELLIGENCE (AI) ON LEARNING INNOVATION - Sahat Renol HS; Selvita Eka Eviana Purba (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The development of Artificial Intelligence (AI) has brought significant transformation to the field of education. This study aims to review the impact of AI on learning innovation through a literature analysis. The findings indicate that AI contributes to the personalization of learning, operational efficiency, and the enhancement of educational accessibility. Technologies such as educational chatbots, intelligent tutoring systems (ITS), and adaptive learning platforms create more interactive and effective learning experiences. However, the implementation of AI also faces challenges related to ethics, data privacy protection, the digital divide, potential algorithmic bias, and educators' readiness. Nevertheless, the role of teachers remains crucial in guiding students and fostering character values. The transformation of learning models through AI opens opportunities to create more inclusive and effective educational experiences, capable of transcending traditional boundaries and providing students worldwide with access to knowledge and skills relevant to contemporary developments.